A Clean Economic Dispatch of PV Energy Storage Connected to Grid Based on LHS-SR-GAMS Technology - Liu Jiang-Tao; Wang Hai-Yun; Luo Jian-Chun; Luo Qing; Chen Xing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
PV output uncertainty, the PV scheduling problem has become urgent. The combined energy storage and PV can solve effectively the problem. We established the joint energy-saving economic scheduling model on PV- Storage generation, which mainly included the penalty model about PV positive deviation output and the penalty model about PV negative deviation output and "overflowing negative revenue" model. Considering the uncertainty of the PV output, this paper analyzed the prediction error distribution characteristics about PV output by the probability density estimate method. Based on the LHS (Latin hypercube sampling) –SR (scenes reduce) technology, PV uncertain output is converted into a finite PV output scenes under different probability conditions. Finally, we used the PV output scenarios as the input data, and we solved the proposed Model based on GAMS (General Algebraic Model System) software, which the optimization goal is the joint expectation maximum power generation benefit. Results show that the proposed method is effective, and had good engineering application value.